University Students’ Perceptions and Attitudes Towards Telemental Health Clinics: The Future of Young Adult Health - Alherz, Anhar; Almousa, Dana A.; Aldossary, Rahaf A.; Alali, Zahrah H.; Alshabib, Maryam H.; Mousa, Ola (European Journal of Applied Sciences, 2023)
Background: Recent years have seen a rapid advance in digital health technologies and apps. This era of digital services will see it play a greater role in transforming health care. In recent years, mental health problems have become increasingly prevalent among young adults attending universities. Universities students are more likely to suffer from psychological distress and mental illness than nonstudents. This study examines undergraduate university students’ perceptions and attitudes toward telemental health, as well as its features. Methods: An online survey was administered to undergraduates at King Faisal University, Saudi Arabia as part of a cross-sectional study. Their invitations to the web-based survey were sent between September and December 2022. Results: The study included 384 participants in total. 165 (43% of the participants) were in university colleges at the 4th level or higher. The majority of participants (214/55.7%) came from non-health colleges. There were 269 female students (70.1%) in the study. The average knowledge level about telemental health clinics is 3.70, which indicates a high level of knowledge. The attitude mean score for telemental health clinics is 3.59, which is considered to be a high "positive" level. Conclusion: Digital mental health technologies are widely popular among young people both inside and outside of youth mental health services. Additionally, they expressed a positive attitude toward its use. In spite of the majority of youths being willing to consider virtual services, many youths have concerns about confidentiality. In relation to youth mental health, it is important to understand how young people view digital mental health interventions.